The HD 217107 planetary system: Twenty years of radial velocity measurements. Issue 9 (11th October 2020) - Giovinazzi, Mark R.; Blake, Cullen H.; Eastman, Jason D.; Wright, Jason; McCrady, Nate; Wittenmyer, Rob; Johnson, John A.; Plavchan, Peter; Sliski, David H.; Wilson, Maurice L.; Johnson, Samson A.; Horner, Jonathan; et al.
Abstract: The hot Jupiter HD 217107 b was one of the first exoplanets detected using the radial velocity (RV) method, originally reported in the literature in 1999. Today, precise RV measurements of this system span more than 20 years, and there is clear evidence of a longer‐period companion, HD 217107 c. Interestingly, both the short‐period planet ( P b  ∼ 7.13 d) and long‐period planet ( P c  ∼ 5059 d) have significantly eccentric orbits ( e b  ∼ 0.13 and e c  ∼ 0.40). We present 42 additional RV measurements of this system obtained with the MINERVA telescope array and carry out a joint analysis with previously published RV measurements from four different facilities. We confirm and refine the previously reported orbit of the long‐period companion. HD 217107 b is one of a relatively small number of hot Jupiters with an eccentric orbit, opening up the possibility of detecting the precession of the planetary orbit due to general relativistic effects and perturbations from other planets in the system. In this case, the argument of periastron, ω, is predicted to change at the level of ∼0.8 ∘ century −1 . Despite the long time baseline of our observations and the high quality of the RV measurements, we are only able to constrain the precession to be ω ˙ < 65.9 ∘ century −1 . We discuss the limitations of detecting the subtle effects of precession in exoplanet orbits using RV data.